The success of bank mergers revisited: an assessment based on a matching strategy - Frank Heid; Andreas Behr (Deutsche Bundesbank, 2008)
The question of whether or not mergers and acquisitions have helped to enhance banks' efficiency and profitability has not yet been conclusively resolved in the literature. We argue that this is partly due to the severe methodological problems involved. In this study, we analyze the effect of German bank mergers in the period 1995-2000 on banks' profitability and cost efficiency. We suggest a new matching strategy to control for the selection effects arising from the fact that predominantly under-performing banks engage in mergers. Our results indicate a neutral effect of mergers on profitability and a positive effect on cost efficiency. Comparing our results with those obtained from a naive performance comparison of merging and non-merging banks indicates a severe negative selection bias with regard to the former.
Keywords: G34; G21; 330; Bank mergers; performance measurement; propensity score matching; Bank; Fusion; Übernahme; Unternehmensentwicklung; Rentabilität; Wirtschaftliche Effizienz; Betriebsvergleich; Matching; Deutschland